PENGGUNAAN MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VI SDN 010 JAYA MUKTI - Elpis (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2017)
This study aims to improve learning outcomes through the use of image media. This research is a class action research, the subject of research is the students of class VI SDN 010 Jaya Mukti. This study was conducted in two cycles, each cycle is implemented based on four stages: planning, implementation, observation, and reflection. The result of the study showed that the IPS learning achievement increased in the first cycle of student learning outcomes was 80.77% and in cycle II increased up to 85.08. Student learning completeness in classical equal to 88,46% in cycle I and 100% in cycle II. Based on the results of the above research, it can be concluded that the use of image media can improve the learning outcomes of IPS students class VI SDN 010 Jaya Mukti.